Quality attributes of fresh-cut, bagged romaine lettuce exposed to specific electron beam doses - Howie, Kendall A.; Pillai, Suresh D. (Frontiers in Food Science and Technology, 2025)
IntroductionThis study evaluated the effects of specific electron beam (eBeam) doses between 1 kGy and 4 kGy on the quality attributes of fresh-cut romaine lettuce that focused on color, texture, moisture retention, and odor during a 14-day storage period at 7°C.Materials and methodsSelected quality attributes were analyzed using instrumental color readings and a subjective appearance scoring rubric provided by a major U.S. supermarket chain to replicate their real-world evaluation process.ResultsElectron beam dose-mapping treatments confirmed uniform dose delivery, ensuring reliability in experimental outcomes. Colorimetric analyses showed that lower doses (1 kGy–2 kGy) preserved lightness (L*), yellowness (b*), and minimized green color loss (a*) while higher doses (3 kGy–4 kGy) resulted in significant darkening, yellowing, and degreening over time. Subjective evaluations revealed that 1 kGy and 2 kGy treatments maintained color stability, texture, and moisture, with minimal off odor development, outperforming both untreated and higher-dose samples. In contrast, lettuce samples exposed to higher doses (3 kGy and 4 kGy) exhibited pronounced browning, wilting, moisture losses, and off-odors by day 14, indicative of dose-related tissue damage and subsequent spoilage mechanisms.ConclusionsThese findings demonstrate the critical importance of dose optimization in preserving the quality of fresh-cut produce, with low-dose treatments effectively extending shelf life. The upper dose of 2 kGy can result in significant improvements in the microbiological safety of lettuce without compromising lettuce quality.